The Role of the Department of Industry and Trade in Protecting Consumer Interest in Bengkulu City - Jaka Adi Setiawan; Mikho Ardinata; Ahmad Dasan (Fakultas Hukum Dehasen, 2022)
Consumer protection is an inseparable part of a healthy business. In a healthy business activity, there is a balance of legal protection between consumers and business behavior. The absence of consumer protection is in a weak position, especially if the product produced is a limited product type, so that business actors can abuse their position by monopolizing marketing production, this of course will be very detrimental to consumers. Consumer protection is in the public interest, therefore it is a hope for all people in every country in the world to be able to make it happen. The form of consumer protection is from various interrelated relationships. The relationship between consumers, business actors and the government. Consumer protection is an inseparable part of healthy business activities. In healthy business activities there is a balance of legal protection between consumers and business actors. this is the background to the problem of the role of the industry and trade service in protecting the interests of consumers in the city of Bengkulu which has been regulated in Indonesia according to Law Number 8 of 1999 concerning Consumer Protection. Therefore, researchers are interested in conducting thesis research with the title